A Study of Atypical Manifestations of Enteric Fever in Childern - Shakya, K. N.; Baral, M. R.; Shrestha, R. (Journal of Nepal Health Research Council, 2009)
Not uploaded.Key Words: Enteric fever; Atypical features; Susceptibility patternDOI: 10.3126/jnhrc.v6i1.2436Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 1-4